Cellular response to alpha-gliadin in untreated coeliac disease. - O'FARRELLY, CLIONA (My University, 1982)
An improved technique for the detection of alpha-gliadin sensitised mononuclear cells in the peripheral blood of untreated coeliac patients is described. This method is a modification of the direct LMIF assay, and involves exposure of lymphocytes to alpha-gliadin and the assay of the resultant lymphokine produced using normal leucocytes as indicator cells. All untreated coeliac patients, 14 of 15 treated patients, and two of 28 controls responded to alpha-gliadin. The direct LMIF assay in comparison is less sensitive, and detected sensitivity to alpha-gliadin in only four out of eight patients with untreated coeliac disease. Use of the indirect LMIF technique demonstrates that in untreated as well as treated coeliac patients there are cells sensitised to alpha-gliadin circulating in the peripheral blood. These findings may have pathogenic and diagnostic significance.
PUBLISHED
Keywords: detection of alpha-gliadin sensitised mononuclear cells; detection of alpha-gliadin sensitised mononuclear cells; Immunology, Inflammation & Infection